The Impact Of Product Quality, Service Quality, And Store Atmosphere On Purchase Decisions And Their Effect On Customer Satisfaction For Santri Packaged Drinking Water At Basmalah Store, Sumenep - Muhammad Wasul; Rahayu Lestari (Jurnal Ekonomi, 2024)
This study aims to determine and analyze the effect of product quality, service quality and store atmosphere on purchasing decisions and their impact on customer satisfaction for santri bottled drinking water products at the Basmalah Sumenep store. The population used is 100 respondents who live in Sumenep and consume santri bottled drinking water. The sampling technique uses purposive sampling, namely making the entire population as a sample, namely 100 customers. While this study uses the Structural Equation Modeling (SEM) model analysis tool. Testing the structural model in PLS was carried out with the help of SmartPLS Ver software. 3.29. The results showed that the Product Quality variable has a positive and significant effect on Purchasing Decisions, the service quality variable has a positive and significant effect on Purchasing Decisions, the Store Atmosphere variable has a positive and significant effect on Purchasing Decisions and the Purchasing Decision variable has a positive and significant effect on Customer Satisfaction.